Enhanced energy and resource recovery via synergistic catalytic pyrolysis of byproducts from thermal processing of wastewater solids. (November 2021) - Liu, Zhongzhe; Hughes, Matthew; Tong, Yiran; Zhou, Jizhi; Kreutter, William; Valtierra, Danny; Singer, Simcha; Zitomer, Daniel; McNamara, Patrick
Abstract: Wastewater sludge drying and incineration are conventional solids handling processes that are sometimes employed in water resource reclamation facilities. However, these two processes generate byproducts, sludge drying chaff and sludge incinerator ash, which are landfilled without taking advantage of their value. To gain value from these byproducts, a new synergistic catalytic pyrolysis process using chaff and ash was investigated in this study to improve energy production (i.e. generating a high yield pyrolysis gas) and generate useful products. Ash was used as a catalyst to decrease bio-oil that is corrosive and challenging for combustion in standard equipment, while increasing pyrolysis gas yield and energy for easier energy recovery. Ash increased the pyrolysis gas yield by 50% and product energy by nearly two-fold at the highest ash loading. The bio-oil volume was greatly reduced and contained fewer constituents based on GC-MS and GC-FID analyses. The product energy shifted from bio-oil to pyrolysis gas, which is relatively clean and easier for onsite energy recovery. Ca and Fe content in ash likely plays the catalytic role. Graphical abstract: Image 1 Highlights: Sludge drying chaff and sludge incinerator ash were synergistically pyrolyzed. Sludge incinerator ash as a catalyst increased pyrolysis gas yield and energy. Sludge incinerator ash decomposed bio-oil to cleaner gas for easier energy recovery. Catalyzed bio-oil contained lower heavy hydrocarbons. Ca and Fe content in sludge incinerator ash likely plays important catalytic role.